Bioprospecting roots, stem and leaves extracts of Berberis baluchistanica Ahrendt. (Berberidaceae) as a natural source of biopharmaceuticals - Siraj Uddin; Luqman Bin Safdar; Iram Fatima; Javed Iqbal; Saleem Ahmad; Banzeer Ahsan Abbasi; Umar Masood Quraishi (Journal of Taibah University for Science, 2022)
The present study was designed to explore the biological potential of aerial parts of Berberis baluchistanica. HPLC analysis revealed the highest berberine content in leaves (19453.15 ppm) followed by roots (3225.12ppm) and stem (29.11ppm). Phenolics, flavonoids, tannins, DPPH inhibition activity and total antioxidant capacity are reported in root, leaf and stem extracts. Antihaemolytic assay displayed the highest (97%) inhibition potential of extracts against H2O2-induced haemolysis than heat-induced haemolysis (75%). The highest DNA protection activity was observed in root and leaves extracts while the antimicrobial potential was recorded highest in the leaves extract against Staphylococcus aureus (23.00 ± 1.0 mm) and Klebsiella pneumonia (19.67 ± 0.2 mm). Similarly, brine shrimp cytotoxicity potential was observed highest in root extract (LC50 – 10.04 ppm) and the allelopathic potential was confirmed by radish seed phytotoxicity assay. Overall, results suggest a remarkable nutritional and biological potential B. baluchistanica, especially areal parts can help to preserve the endemic plants by discouraging the use of roots.